1996
DOI: 10.1111/j.1365-2621.1996.tb10975.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Analysis and Consumer Acceptance of Irradiated Boneless Pork Chops

Abstract: Flavor, texture, and aroma were determined for chilled (3 ‫ע‬ 2ЊC) and frozen (Ϫ17 ‫ע‬ 3ЊC) boneless pork chops packaged in vacuum or air and exposed to an absorbed dose of 0, 1.5, or 2.5 kGy (chilled) or 0, 2.5, or 3.85 kGy (frozen) of electron beam and cobalt 60 irradiation. Irradiation (≤3.85 kGy) had minimal effects on aroma, flavor, and textural attributes in chilled and frozen boneless pork chops. Irradiation source had limited effects and packaging type had the greatest influence. Consumers reported no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
3
10
0
1
Order By: Relevance
“…Dark meat irradiated in the frozen state had no difference from the control (Hashim et al, 1995). Luchsinger et al (1996) found that the textural attributes of chilled boneless pork chops were not affected by irradiation dose levels of 1.5 and 2.5 kGy. Beggs et al (1997) found Day 32 0 kGy 77 AE 4 0 1 4 AE 2 1 9 AE 2 1 kGy 77 AE 4 0 1 4 AE 2 1 9 AE 5 2 kGy 77 AE 3 0 1 3 AE 2 1 9 AE 1 3 kGy 77 AE 3 0 1 4 AE 2 1 7 AE 1 a Ratings are based on 150-mm unstructured line scales with anchors at 12.5 and 137.5.…”
Section: Texture Attributesmentioning
confidence: 91%
See 2 more Smart Citations
“…Dark meat irradiated in the frozen state had no difference from the control (Hashim et al, 1995). Luchsinger et al (1996) found that the textural attributes of chilled boneless pork chops were not affected by irradiation dose levels of 1.5 and 2.5 kGy. Beggs et al (1997) found Day 32 0 kGy 77 AE 4 0 1 4 AE 2 1 9 AE 2 1 kGy 77 AE 4 0 1 4 AE 2 1 9 AE 5 2 kGy 77 AE 3 0 1 3 AE 2 1 9 AE 1 3 kGy 77 AE 3 0 1 4 AE 2 1 7 AE 1 a Ratings are based on 150-mm unstructured line scales with anchors at 12.5 and 137.5.…”
Section: Texture Attributesmentioning
confidence: 91%
“…However, in studies on raw dark poultry meat (Hashim, Resurreccion, & McWatters, 1995), the aroma of dark chicken meat irradiated from the refrigerated state at 1.6-2.86 kGy, increased in intensities of fresh chikeny, bloody and sweet aromatic aromas. Wheeler, Shackelford, and Koohmaraie (1999) found that control patties had a more intense ground beef aroma and less of an off aroma than irradiated (3.0 and 4.5 kGy) patties, whereas, Luchsinger et al(1996) found that raw and cooked pork aroma attributes were not influenced by irradiation dose levels.…”
Section: Total Aromamentioning
confidence: 94%
See 1 more Smart Citation
“…La calidad de la carne puede verse más o menos afectada, dependiendo de la dosis, temperatura y atmósfera durante el tratamiento y de las condiciones de almacenamiento. En carne cruda, pueden desarrollarse olores extraños que desaparecen al cocinar (Luchsinger et al 1996). Pueden producirse también cambios de color: irradiando en ausencia de oxígeno se acentúa el brillo de los colores (Lebepe et al 1990), mientras que en presencia de oxígeno se producen decoloraciones (Grant y Patterson, 1991a).…”
Section: En Productos Cárnicosunclassified
“…In raw meat, odors can be developed or disappear during cooking (Luchsinger et al, 1996, Hashim et al,1995and Ahn et al, 1998. Most of the chemical changes in irradiated meat are associated with free radical reactions (Ahn and Lee, 2004).…”
Section: Samples and Sample Treatmentmentioning
confidence: 99%